Contribution of Muslim Scientists to the world: an overview of some selected fields - Afridi, Muhammad Adil Khan (Revelation and Science, IIUM, 2013)
The Qur’Én which is the foundation of Islamic teachings gives the utmost emphasize on pursuing knowledge. Muslim scholars from the past were very much aware of this instruction given by Allah (s. w. t.) and they were very captivated by it. They developed many ideas and theories in the field of knowledge. This paper will try to shed somelight on a few works that have been carried out by Muslim scholars. However, it focuses on the contributions of Muslim scholars in Mathematics, Physics and Medicine only.It is hoped that, by remembering all those Muslim heroes and their contributions; contemporary Muslim societies, particularly muslim scholars will be inspired.